2023
DOI: 10.1080/15476286.2023.2257471
|View full text |Cite
|
Sign up to set email alerts
|

Anticodon sequence determines the impact of mistranslating tRNA Ala variants

Ecaterina Cozma,
Megha Rao,
Madison Dusick
et al.

Abstract: Transfer RNAs (tRNAs) maintain translation fidelity through accurate charging by their cognate aminoacyl-tRNA synthetase and codon:anticodon base pairing with the mRNA at the ribosome. Mistranslation occurs when an amino acid not specified by the genetic message is incorporated into proteins and has applications in biotechnology, therapeutics and is relevant to disease. Since the alanyl-tRNA synthetase uniquely recognizes a G3:U70 base pair in tRNA Ala and the anticodon plays no role in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 90 publications
1
2
0
Order By: Relevance
“…Indeed, we noted a correlation between the number of codons read and growth defect just for tRNAs for Gly and Arg. Similar observations were found in a library of tRNA Ala variants in yeast . Rather, we found that the nature of the amino acid replacement according to amino acid similarity and the strength of the anticodon–codon interaction were the dominant factors that contribute to the impact of missense suppressor tRNAs on cell growth …”
Section: Misreading the Genetic Code With Missense Suppressor Trnassupporting
confidence: 86%
See 2 more Smart Citations
“…Indeed, we noted a correlation between the number of codons read and growth defect just for tRNAs for Gly and Arg. Similar observations were found in a library of tRNA Ala variants in yeast . Rather, we found that the nature of the amino acid replacement according to amino acid similarity and the strength of the anticodon–codon interaction were the dominant factors that contribute to the impact of missense suppressor tRNAs on cell growth …”
Section: Misreading the Genetic Code With Missense Suppressor Trnassupporting
confidence: 86%
“…Similar observations were found in a library of tRNA Ala variants in yeast. 206 Rather, we found that the nature of the amino acid replacement according to amino acid similarity and the strength of the anticodon−codon interaction were the dominant factors that contribute to the impact of missense suppressor tRNAs on cell growth. 45 As noted above, mistranslation does not always lead to detrimental changes in global protein homeostasis.…”
Section: Considerations and Applications Of Missense Suppressor Trnas...mentioning
confidence: 79%
See 1 more Smart Citation